Hydrothermal remobilization of subseafloor sulfide mineralization along mid-ocean ridges contributes to the global oceanic zinc isotopic mass balance - Liao, Shili; Tao, Chunhui; Wen, Hanjie; Yang, Weifang; Liu, Jia; Jamieson, John W.; Dias, Ágata Alveirinho; Zhu, Chuanwei; Liang, Jin; Li, Wei; Ding, Teng; Li, Xiaohu; et al. (Geochimica et Cosmochimica Acta, 2022)
Hydrothermal activity on mid-ocean ridges is an important mechanism for the delivery of Zn from the mantle to the surface environment. Zinc isotopic fractionation during hydrothermal activity is mainly controlled by the precipitation of Zn-bearing sulfide minerals, in which isotopically light Zn is preferentially retained in solid phases rather than in solution during mineral precipitation. Thus, seafloor hydrothermal activity is expected to supply isotopically heavy Zn to the ocean. Here, we studied sulfide-rich samples from the Duanqiao-1 hydrothermal field, located on the Southwest Indian Ridge. We report that, at the hand-specimen scale, late-stage conduit sulfide material has lower δ66Zn values (−0.05 ± 0.15 ‰; n = 19) than early-stage material (+0.13 ± 0.15 ‰; n = 10). These lower values correlate with enrichments in Pb, As, Cd, and Ag, and elevated δ34S values. We attribute the low δ66Zn values to the remobilization of earlier sub-seafloor Zn-rich mineralization. Based on endmember mass balance calculations, and an assumption of a fractionation factor (αZnS-Sol.) of about 0.9997 between sphalerite and its parent solution, the remobilized Zn was found consist of about 1/3 to 2/3 of the total Zn in the fluid that formed the conduit samples. Our study suggests that late-stage subsurface hydrothermal remobilization may release isotopically-light Zn to the ocean, and that this process may be common along mid-ocean ridges, thus increasing the size of the previously identified isotopically light Zn sink in the ocean.
Keywords: Hydrothermal activity; Mid ocean ridge; Subsurface remobilization; Zinc isotopic mass balance

Occurrence and precipitation mechanism of silver in pyrite from chimney fragments in the Edmond hydrothermal field, Central Indian Ridge - Zhang, Huichao; Chen, Kean; Tao, Chunhui; Alveirinho Dias, Ágata; Liang, Jin; Yang, Weifang; Liao, Shili; An, Fang; Yin, Bohao; Sun, Chuanqiang (Ore Geology Reviews, 2023)